Tobacco Smoking Among First Nations Youth Living on Reserve and in Northern Communities: A Mixed Methods Study - Wright, Laura; Dell, Colleen A. (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2020)
The prevalence of tobacco smoking among First Nations youth living on reserve and in Northern communities is significantly higher than off-reserve Indigenous youth in Southern communities and non-Indigenous youth, although the majority do not smoke. Using a mixed-methods approach, we examine factors that support on-reserve First Nations youth’s resilience to smoking. Logistic regression analyses using data from the nationally representative First Nations Regional Early Childhood, Education, and Employment Survey suggest that not using other substances, having friends who do not smoke or use other substances, and having good mental health is associated with not smoking. A review of select community initiatives and in-depth interviews with First Nations anti-tobacco initiative managers and frontline workers about the initiatives also revealed the need for gender- and community-specific programming, recognition of Indigenous social determinants of health, and addressing the normalization of smoking in some community contexts.